Patterns of deliveries in a Brazilian birth cohort: almost universal cesarean sections for the better-off Padrones de partos en una cohorte de nacimientos: cesáreas casi universales para los riesgos Padrões dos partos em uma coorte de nascimentos: cesarianas quase universais para os ricos - Aluísio J D Barros; Iná S Santos; Alicia Matijasevich; Marlos Rodrigues Domingues; Mariângela Silveira; Fernando C Barros; Cesar G Victora (Universidade de São Paulo, 2011)
OBJECTIVE: To describe the patterns of deliveries in a birth cohort and to compare vaginal and cesarean section deliveries. METHODS: All children born to mothers from the urban area of Pelotas, Brazil, in 2004, were recruited for a birth cohort study. Mothers were contacted and interviewed during their hospital stay when extensive information on the gestation, the birth and the newborn, along with maternal health history and family characteristics was collected. Maternal characteristics and childbirth care financing - either private or public healthcare (SUS) patients - were the main factors investigated along with a description of C-sections distribution according to day of the week and delivery time. Standard descriptive techniques, Χ² tests for comparing proportions and Poisson regression to explore the independent effect of C-section predictors were the methods used. RESULTS: The overall C-section rate was 45%, 36% among SUS and 81% among private patients, where 35% of C-sections were reported elective. C-sections were more frequent on Tuesdays and Wednesdays, reducing by about a third on Sundays, while normal deliveries had a uniform distribution along the week. Delivery time for C-sections was markedly different among public and private patients. Maternal schooling was positively associated with C-section among SUS patients, but not among private patients. CONCLUSIONS: C-sections were almost universal among the wealthier mothers, and strongly related to maternal education among SUS patients. The patterns we describe are compatible with the idea that C-sections are largely done to suit the doctor's schedule. Drastic action is called for to change the current situation. OBJETIVO: Describir el padrón de los partos en una cohorte de nacimientos, comparando partos normales y cesáreos. MÉTODOS: Todos los recién nacidos de moradoras de área urbana de Pelotas (Sur de Brasil) en 2004 fueron reclutados para una cohorte de nacimientos. Las madres fueron entrevistadas aún en el hospital, cuando informaciones detalladas de la gestación, el parto y el recién nacido, junto con una historia de salud materna y características de la familia fueron colectadas. Características maternas y el financiamiento del parto fueron los principales factores estudiados. También se hizo descripción de la distribución de las cesáreas por hora del día y día de la semana. Técnicas de padrón de análisis descriptivo y pruebas chi-cuadrado para comparar proporciones y regresión Poisson para explorar el efecto independiente de predictores de la cesárea fueron los métodos utilizados. RESULTADOS: La tasa global de cesáreas fue de 45%, 36% entre pacientes del servicio público y 81% en el servicio privado, donde se relató que 35% de las cesáreas fueron electivas. Las cesáreas fueron más frecuentes martes y miércoles, con una reducción de cerca de un tercio los domingos, mientras que los partos normales presentaron distribución uniforme a lo largo de la semana. El horario de las cesáreas en el servicio público y en el privado fue muy diferente. La escolaridad materna se asoció positivamente con la cesárea entre las madres del servicio público, pero no del privado. CONCLUSIONES: La cesárea fue muy frecuente entre las madres más ricas, y fuertemente asociada con la escolaridad materna entre pacientes del servicio público. Los padrones descritos son compatibles con la hipótesis de que las cesáreas son hechas, en gran parte, para atender la conveniencia de las agendas de los médicos. La situación actual sólo será revertida con políticas radicales. OBJETIVO: Descrever o padrão dos partos em uma coorte de nascimentos, comparando partos normais e cesarianos. MÉTODOS: Todos os recém-nascidos de moradoras da área urbana de Pelotas (RS) em 2004 foram recrutados para uma coorte de nascimentos. As mães foram entrevistadas ainda no hospital, quando informações detalhadas sobre a gestação, o parto e o recém-nascido, junto com um histórico da saúde materna e características da família foram coletadas. Características maternas e o financiamento do parto foram os principais fatores estudados. Também se fez uma descrição da distribuição das cesáreas por hora do dia e dia da semana. Técnicas padrão de análise descritiva e testes qui-quadrado para comparar proporções e regressão Poisson para explorar o efeito independente de preditores da cesárea foram os métodos utilizados. RESULTADOS: A taxa global de cesarianas foi de 45%, 36% entre pacientes do SUS e 81% no serviço privado, onde se relatou que 35% das cesarianas foram eletivas. As cesarianas foram mais freqüentes nas terças e quartas-feiras, com uma redução de cerca de um terço aos domingos, enquanto os partos normais apresentaram distribuição uniforme ao longo da semana. O horário das cesarianas no setor público e no privado foi muito diferente. A escolaridade materna se associou positivamente com a cesariana entre as mães do serviço público, mas não do privado. CONCLUSÕES: A cesariana foi muito freqüente entre as mães mais ricas, e fortemente associada com a escolaridade materna entre pacientes do SUS. Os padrões descritos são compatíveis com a hipótese de que as cesáreas são feitas, em grande parte, para atender a conveniência das agendas dos médicos. A situação atual só será revertida com políticas radicais.